Complex therapy against toxascariosis of caged silver foxes - A. P. Konovalov; I. I. Tsepilova; F. I. Vasilevich (Российский паразитологический журнал, 2021)
The purpose of the research is evaluating the efficacy of complex therapy using dironet, lactobifadol and keratin food supplement (DLK) against toxascariosis of the arctic fox.Materials and methods. To determine the helminth fauna in the conditions of Vyatka Fur Breeding Farm, 61 females silver fox and 55 females voilevoy arctic fox were used as study objects. To conduct complex therapy against toxascariosis, the study object was 24 females culled from the breeding herd, spontaneously infected with toxascariosis and being clinically healthy. The morphological and biochemical blood parameters in female foxes were determined before and after dehelminthization, and control weighing of animals from experimental groups was carried out before and after the experiment.Results and discussion. Of the studied 116 fur-bearing animals, 26 (22.4%) were infected with Toxascaris leonina. Infection rate of Toxascaris sp. in silver fox females aged 5–7 years was 42.6% when 7-9 eggs were found in one microscope field (magnification 7 × 9). Infection with Toxascaris sp. affects on the body weight of infected animals. The females silver fox from the second experimental group infected with Toxascaris sp., which were not treated, had an average live weight of 1.3 kg less (16.6%) as compared to the control. The complex therapy with the DLK treatment-and-prophylactic complex contributed to the improved metabolic processes and digestion. The applicability of the DLK treatment-and-prophylactic complex for therapy against toxascariosis was proved.